Implementasi Pendekatan Pendidikan Matematika Realistik Indonesia (PMRI) Pada konsep Merdeka Belajar. - Gerhajun Fredy Purba (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2022)
The Minister of Education issued a policy of independent learning to become a new challenge for educators in learning activities. The application of independent learning is an effort given to each educational unit to be free to make innovations and of course it is adjusted according to the area of ​​each educational unit as an open learning process from home which can later provide a learning experience without being demanded by completeness standards or graduation standards. . This policy makes education also take various approaches to improve student learning outcomes. The application of the right learning approach is still far from what is expected, so that student learning outcomes are often not optimal. This can be caused by the efforts and approaches taken are not less precise, resulting in low interest, motivation and understanding of students towards mathematical material. This makes teachers have to consider an appropriate approach that can be applied in the learning process activities which are later expected to improve learning outcomes, especially during the independent learning period at the level. One of the efforts made is to implement an Indonesian Realistic Mathematics Education Approach (PMRI) in a series of learning process activities, especially during the government's policy of Merdeka Learning. The method of writing this article is to use a literature study of scientific articles, papers, proceedings, and books that are in accordance with the research focus.